112. H max/M max ratio and H-reflex recovery curve in patients affected by Multiple Sclerosis and spasticity. Issue 4 (April 2016) - Alessandrini, L.; Donato, F.; Turri, M.; Romito, S.; Moretto, G.; Squintani, G.
Abstract : Spasticity is classically defined as an increase of the velocity dependent stretch reflex and the H-reflex (HR) is commonly used to study the excitability of spinal motor circuitry. Some features of upper neuron syndrome like spasticity are associated with H-reflex alterations and different patterns of HR abnormalities have been reported. However, the simple evaluation of the soleus HR amplitude and H max/ M max ratio may lack clinical and physiological relevance when approaching spasticity. We studied HR stimulating tibial nerve at popliteal fossa and recording at soleus muscle bilaterally in 16 subjects with Multiple Sclerosis (MS) and spasticity. H max/ M max, recovery cycle (HRC) of HR with ISI ranging from 5 to 1000 ms were detected and results were compared with age-sex- matched controls. HRS was increased significantly in MS subjects at ISI 500 ms compared to healthy subjects. No difference was detected regarding H / M ratio. Our data demonstrated that HRC is more sensitive than H max/ M max ratio in MS patients affected by spasticity and may represent the neurophysiological correlate of spinal inhibitory interneurons and descending pathways impairment in MS patients with spasticity. These findings could serve as electrophysiological tool to assess spasticity and monitor efficacy of therapeutic interventions.